Implementasi Perencanaan Pembelajaran Mendalam dan Kurikulum Berbasis Cinta pada Mata Pelajaran Fikih di Madrasah Tsanawiyah Negeri 3 Boyolali - Salim, Nur Zaidi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
This study aims to examine the implementation of in-depth learning planning and a love-based curriculum in Islamic jurisprudence (fiqh) at Madrasah Tsanawiyah Negeri 3 Boyolali. The study used a qualitative approach with a case study design, conducted at Madrasah Tsanawiyah Negeri 3 Boyolali. Data were collected through in-depth interviews, classroom observations, and documentation studies, and analyzed using the Miles and Huberman interactive model. The results showed that students who participated in the in-depth learning approach and love-based curriculum experienced significant improvements in critical thinking skills compared to students who received conventional learning. These findings indicate that the in-depth learning approach and love-based curriculum have a positive impact on character development, creativity, and problem-solving, encouraging active and reflective student engagement. Thus, these results strengthen the argument that in-depth learning and a love-based curriculum can be the main foundation for increasing learning motivation, strengthening student character, and creating a more humanistic classroom atmosphere in Islamic jurisprudence (fiqh) at Madrasah Tsanawiyah Negeri 3 Boyolali.